Amphiregulin/epidermal growth factor receptor/hypoxia-inducible factor-1α pathway regulates T helper 9 and T cytotoxic 9 cell response in adult patients with infectious mononucleosis - Yu Li; Lan Li; Weihua Zhang; Ying Gao (Biomolecules & Biomedicine, 2023)
Amphiregulin (AREG)/epidermal growth factor receptor (EGFR) signaling induces hypoxia-inducible factor-1α (HIF-1α), leading to promotion of T helper 9 (Th9) differentiation and anti-tumor functions. However, the role of the AREG/EGFR/HIF-1α pathway in regulating interleukin-9 (IL-9) production by T cells in adult patients with infectious mononucleosis (IM) has not been fully elucidated. Fifty IM patients and 20 controls were enrolled. The percentages of Th9 and T cytotoxic 9 (Tc9) cells, the mRNA relative expressions of the transcription factors of IL-9-secreting T cells, purine-rich nucleic acid binding protein 1 (PU.1) and forkhead box protein O1 (FOXO1), and the levels of IL-9, AREG, EGFR, and HIF-1α were measured. Peripheral blood mononuclear cells from IM patients were stimulated with EGFR inhibitor or exogenous AREG in the presence or absence of anti-HIF-1α. Regulation of the AREG/EGFR/HIF-1α pathway to IL-9 production by T cells was assessed. The percentages of Th9 and Tc9 cells, plasma IL-9 levels, and PU.1 and FOXO1 mRNA expressions were elevated in IM patients. Plasma levels of AREG and HIF-1α were also increased in IM patients. AREG levels correlated positively with the percentages of Th9 and Tc9 cells in IM patients. Inhibition of EGFR suppressed IL-9-producing T cell differentiation and HIF-1α production. Exogenous AREG stimulation not only induced EGFR and HIF-1α expression but also promoted IL-9-secreting T cell differentiation. Neutralization of HIF-1α abrogated AREG/EGFR-induced Th9 and Tc9 differentiation in IM patients. The current data suggested that the AREG/EGFR/HIF-1α pathway contributed to the elevation of Th9 and Tc9 differentiation in IM patients.